The Influence of Audio Visual Technique Information Services to Improve Knowledge of The Impact of Early Marriage - Putri, Indri; Irman, Irman; Carol, Tuomi (Yayasan Minang Darussalam, 2023)
The main problem in this research is students' knowledge of the impact of early marriage. The purpose of this study was to examine the effect of audio-visual technical information services on increasing knowledge of the impact of early marriage. This type of research is quantitative using experimental methods. The research design used is pre-experimental design with type the one group pretest-posttest design. The results of this study indicate that audio-visual technical information services have a significant effect on increasing students' knowledge of the impact of early marriage. This can be seen from the results of the analysis which shows that t count ? t table.